2022
DOI: 10.1080/14786419.2022.2089138
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of myricetin against acute liver failure via inhibiting inflammation and regulating oxidative stress via Nrf2 signaling

Abstract: This study aimed to investigate the protective effects and mechanisms of myricetin on acute liver failure in mice induced by lipopolysaccharide (LPS)/D-galactosamine (D-Gal). Our results showed myricetin (25, 50 and 100 mg/kg) pretreatment significantly improved the pathological changes of liver tissues, decreased serum ALT and AST (p < 0.001) induced by LPS/D-GalN. Moreover, MDA and MPO levels were reduced (p < 0.001), CAT and SOD activities were increased (p < 0.001) with myricetin (50 and 100 mg/kg) pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Finally, it is worth mentioning that, as explained in detail in a previous study, practically all the secondary metabolites existing in Sechium edule modulate the expression of Nrf2 mRNA; for example, cucurbitacins, naringenin, and caffeic and ferulic acids have been related to an increase in Nrf2 gene expression and inhibition of NFκB-mediated signaling [64][65][66][67]. Apigenin, myricetin, and gallic acid improve translocation and/or nuclear accumulation [68][69][70]. Quercetin only temporarily stimulates its expression [71].…”
Section: Discussionmentioning
confidence: 89%
“…Finally, it is worth mentioning that, as explained in detail in a previous study, practically all the secondary metabolites existing in Sechium edule modulate the expression of Nrf2 mRNA; for example, cucurbitacins, naringenin, and caffeic and ferulic acids have been related to an increase in Nrf2 gene expression and inhibition of NFκB-mediated signaling [64][65][66][67]. Apigenin, myricetin, and gallic acid improve translocation and/or nuclear accumulation [68][69][70]. Quercetin only temporarily stimulates its expression [71].…”
Section: Discussionmentioning
confidence: 89%
“…significantly elevated the protein expression of Nrf2. [77] Myricetin exhibited protective effects against fulminant hepatitis induced by lipopolysaccharide and D-galactosamine. This protection involved the inhibition of hepatic apoptosis, inflammation, and oxidative stress.…”
Section: Pharmacological Effects Of Myricetin By Nrf2 Signaling Pathwaymentioning
confidence: 99%
“…Myricetin (0, 5, 10, 15, 20 μM) Nucleus pulposus cells (NPCs) Activated Nrf2 and attenuated inflammatory factors production [76] 14. Acute liver failure Myricetin (25, 50 and 100 mg/kg) Male BALB/c mice Decreased ALT and AST, increased CAT and SOD activities, TNF-α and IL-6 via elevated Nrf2 pathway [77] glycogen synthase kinase (GSK) 3β is pivotal in the process of blood clot formation under conditions of elevated shear stress. [83] Furthermore, myricetin demonstrated significant inhibition of the activation of the PI3K/AKT/GSK3β pathway in platelets stimulated by collagen at concentrations of 10, 20 μM, thereby serving as a potent antithrombotic agent.…”
Section: Intervertebral Disc Degeneration (Idd)mentioning
confidence: 99%
“…In the study by Wang et al (2023), myricetin demonstrated a protective effect against acute liver injury induced by LPS/D-GalN (lipopolysaccharide/D-galactosamine) in mice.…”
Section: Attenuation Of Liver Injury and Damagementioning
confidence: 99%